2021
DOI: 10.2340/00015555-3901
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Behaviour and Barriers to Prescription of Biologicals for Treatment of Chronic Inflammatory Skin Diseases in Dermatological Practice in Two German Federal States

Abstract: The globally increasing prevalence of chronic inflammatory skin diseases has substantial costs. Biologicals have become available as therapeutic options, but are encumbered with barriers to prescription. The aim of this study was to evaluate the barriers to prescription of biologicals in the treatment of chronic dermatological diseases. Dermatologists working in private practices in the German federal states of Bavaria and Lower Saxony participated in a cross-sectional study. Economic and legal aspects, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
3
6
0
Order By: Relevance
“…11,16 The rate of patients receiving biologicals was comparable to that of another German study 7 but lower than reported before (8%-11%). 11,16 One explanation may be that this study asked about the proportion among all patients, whereas the other two studies focused on patients with moderate-to-severe AD. Another explanation could be that only dermatologists from Bavaria were considered, who prescribe biologics less commonly compared to dermatologists from other German federal states.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…11,16 The rate of patients receiving biologicals was comparable to that of another German study 7 but lower than reported before (8%-11%). 11,16 One explanation may be that this study asked about the proportion among all patients, whereas the other two studies focused on patients with moderate-to-severe AD. Another explanation could be that only dermatologists from Bavaria were considered, who prescribe biologics less commonly compared to dermatologists from other German federal states.…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, almost one-third of dermatologists were dissatisfied with therapy costs, which were previously shown to be an obstacle for the prescription of emollients and biologicals. 11,16 The rate of patients receiving biologicals was comparable to that of another German study 7 but lower than reported before (8%-11%). 11,16 One explanation may be that this study asked about the proportion among all patients, whereas the other two studies focused on patients with moderate-to-severe AD.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Notably, the financial aspect may cause more unmet medical needs in allergological care in comparison with those in financially more attractive fields of medicine. Financial barriers have been identified as being present in all aspects of care, from the general availability of allergological care, to diagnostics or the prescription of efficient medicine [27, 40]. Although Germany currently has a relatively high number of allergologists, the number of specialists is continually decreasing [7].…”
Section: Discussionmentioning
confidence: 99%